A significant issue faced by Cancer Patients: Unemployment Concern - Ozlu, Zeynep Karaman; Kaya, Merve; Yayla, Aysegul; Eskici, Vesile; Ozlu, Ibrahim; Ozer, Nadiye (Eastern Journal of Medical Sciences, 2019)
Background: As the cancer prevalence rate increases, physical, psychological, and socio-economic problems caused by cancer increase, and the patients’ quality of life is negatively affected. Objective: This study was conducted to determine unemployment concerns faced by cancer patients and the reasons for these concerns. Methods: This was a descriptive study conducted in a tertiary care hospital between March 2016 and May 2017. The study population included all the patients receiving outpatient chemotherapy at a chemotherapy unit in a research hospital at Erzurum. The sample consisted of 405 patients who met the inclusion criteria. A form that was prepared by the researcher based on the literature was used to collect data. The data was analyzed using SPSS 16 and a p<0.05 was considered to be significant. Results: Of the participants, 56% were concerned about losing their jobs. The reasons for this concern were introversion and a decrease in self-confidence during the illness, health insurance not meeting treatment expenses, concerns that the salaries and income level will change during the treatment period, changes in a retirement plan, and facing situations hindering the return to work during the post-treatment period. Conclusion: This study clearly indicates the fear and concern of cancer patients regarding job loss. Occupational organizations and healthcare staff should cooperate to improve the care service.